Advantages of Carbon Nanomaterials in Electrochemical Aptasensors for Food Analysis. Issue 1 (24th October 2017) - Vasilescu, Alina; Hayat, Akhtar; Gáspár, Szilveszter; Marty, Jean‐Louis
Abstract: Electrochemical aptasensors appear as promising tools in food analysis, able to provide sensitive, fast and cost‐effective analysis, with the added advantage of portability. Carbon nanomaterials and in particular carbon nanotubes and graphene are among the nanomaterials most often used to build electrochemical aptasensors due to their good electrical conductivity, large surface area and multiple functionalisation possibilities. This review aims to give an overview of the types of carbon nanomaterials and their composites which have been used to enhance the performance of electrochemical aptasensors. Examples are detailed for the biosensors which were tested with real food samples. In these aptasensors, carbon nanomaterials have played different roles, from facilitating the immobilization of high amounts of aptamer and enhancing the electroactive area of the sensors to roles as nanocarrier for signaling probes in amplification schemes or even as electroactive probes generating the output signal. The survey of recent literature shows a positive evolution towards increased aptasensor testing with food samples. However, many challenges remain related to the better characterization of nanomaterials used, clarifying the roles of specific components in multi‐component nanocomposites and widening the types of food matrices and analytes tested with the aptasensors. Although we are still far from knowing when these novel tools will replace classic analytical methods in food analysis, carbon nanomaterials will certainly continue to play an important role in the design of future electrochemical aptasensors for food analysis. Abstract :